Food Insecurity Status Of Rural Households During the Post Planting Season in Nigeria (2013)
Despite various approaches addressing the challenges of food insecurity in Nigeria, the country is still characterized by chronic food shortages particularly in the rural areas. This is an indication that the problem of food insecurity has not been adequately and critically analyzed. This study examined the food insecurity status of rural households during the post planting season in Nigeria using the recent nationally representative survey data. Results showed that about half of the rural households (49.4%) in Nigeria were food insecure during the post-planting season. Also, econometric analysis confirms that household size, education of household head, access to credit and remittances were among the major factors influencing the food insecurity status of rural households during the period. Thus, intensification of enlightenment on birth control measures, improved access to credit facilities and provision of safety nets for food insecure households during this period is pertinent.